The attitude towards board game usage in interactive learning / Adibah Hussin, Nor Aziah Abd. Kadir, Azniza Zaini and et.al - Hussin, Adibah; Abd. Kadir, Nor Aziah; Zaini, Azniza; Che Hamzah, Hamnah (Universiti Teknologi MARA Cawangan Pahang, 2019)
Today, interactive learning has slowly replaced the traditional method of learning in classroom, which relies on listening to teacher’s lectures, using textbook, memorization of information, figures and equations. Student claims that using traditional method of learning, makes them difficult to understand the content particularly for economics subject. Keeping students motivated and interested during the lesson is a remarkable challenge for the lecturers. Therefore, developed an interactive economics game board named “Catur Ekonomi” to enable students give full attention and interest in learning economics subject. It provides an attractive way of learning economics subjects as the students’ understanding towards this subject could be enhanced and their academic performance could be improved. However, how far this board game really achieved its objective? Hence, this paper investigated the perception and attitude of students on the application of “Catur Ekonomi”. Besides, this paper also identifies the difference of students’ attitude on interactive learning across two demographic factors; gender and academic achievement. The students were given a set of questionnaires after playing the “Catur Ekonomi” and the data were analyzed. The result showed that students enjoy learning using the “Catur Ekonomi” and showed positive attitude towards its applications. On the other hand, both male and female students enjoy using the board game and high achiever students enjoyed more the board game than low achiever students.